Therapeutic Efficacy and Safety of Traditional Chinese Medicine Classic Herbal Formula Longdanxiegan Decoction for Hypertension: A Systematic Review and Meta-Analysis - Xiong, Xing-jiang; Yang, Xiao-chen; Liu, Wei; Duan, Lian; Wang, Peng-qian; You, Hu; Li, Xiao-ke; Wang, Shihan (Frontiers in Pharmacology, 2018)
Background: The traditional Chinese medicine classic herbal formula Longdanxiegan decoction (LDXGD) is widely used for hypertensive patients in China. Objectives: This systematic review and meta-analysis aimed to evaluate the efficacy and safety of LDXGD for hypertension. Methods: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Database, Chinese Scientific Journal Database, Chinese National Knowledge Infrastructure, and Wanfang Database were searched up to February 7, 2017 for randomized control trials in treating hypertension. Results: Nine trials were identified. Compared with antihypertensive drugs, Longdanxiegan decoction plus antihypertensive drugs (LPAD) significantly improved systolic blood pressure (BP) (n = 138; MD = -4.82 mmHg; 95% CI: -7.89 to -1.76; P = 0.002), diastolic BP (n = 138; MD = -2.42 mmHg; 95% CI: -3.22 to -1.62; P < 0.00001), categorical BP (n = 509; RR: 1.26; 95% CI: 1.17 to 1.36; P < 0.00001), hypertension related symptoms (n = 509; RR: 1.31; 95% CI: 1.15 to 1.49; P < 0.0001), and heart rate (n = 138; MD = -2.40 bpm; 95% CI: -4.23 to -0.56; P = 0.01). Beneficial effects but no statistically significant reduction in total cholesterol (n = 138; MD = -0.11 mmol/l; 95% CI: -0.65 to 0.44; P = 0.71), or triglyceride (n = 138; MD = -0.20 mmol/l; 95% CI: -0.46 to 0.07; P = 0.14) was observed in LPAD. Compared with antihypertensive drugs, LDXGD used alone significantly improved systolic BP, diastolic BP and hypertension related symptoms. But there was no difference between LDXGD and antihypertensive drugs on categorical BP (n = 120; RR: 1.09; 95% CI: 0.96 to 1.23; P = 0.18). The safety of LDXGD were still unclear. Conclusions: Due to poor methodological quality of the included trials, as well as potential reporting bias, our review found no conclusive evidence for the effectiveness of LDXGD in treating hypertension. The potential beneficial effects and safety of LDXGD should be assessed in future properly designed trials.